2021
DOI: 10.3390/s21041432
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Torque Deviation of Cylinder Deactivation Engine through 48V Mild-Hybrid Starter-Generator Control

Abstract: Cylinder deactivation (CDA) is an effective technique to improve fuel economy in spark ignition (SI) engines. This technique enhances volumetric efficiency and reduces throttling loss. However, practical implementation is restricted due to torque fluctuations between individual cylinders that cause noise, vibration, and harshness (NVH) issues. To ease torque deviation of the CDA, we propose an in-cylinder pressure based 48V mild-hybrid starter-generator (MHSG) control strategy. The target engine realizes CDA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The dilution effect (C DE ) of the residual EGR or the external EGR influence the laminar flame speed (S L ) [16]. Increasing C DE will reduce the effect of dilution on the S L and thus increase the burn rate.…”
Section: Spark-ignition Turbulent Flame Model (Siturb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The dilution effect (C DE ) of the residual EGR or the external EGR influence the laminar flame speed (S L ) [16]. Increasing C DE will reduce the effect of dilution on the S L and thus increase the burn rate.…”
Section: Spark-ignition Turbulent Flame Model (Siturb)mentioning
confidence: 99%
“…The C FKG and C TFS are magnitude factors of the turbulent flame speed. C FKG has an especially greater influence on the initial combustion velocity with smaller flame radius [16]. Recent direct numerical simulation (DNS) [18] studies have shown that the initial Flame Kernel size and the turbulence structure (flow surrounding the spark plasma, at constant length scales and turbulence intensity) are more important than integral length scale or turbulence intensity for flame growth.…”
Section: Spark-ignition Turbulent Flame Model (Siturb)mentioning
confidence: 99%